Smart Nanovesicles for Drug Targeting and Delivery - Marianecci, Carlotta (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Nanovesicles are highly-promising systems for the delivery and/or targeting of drugs, biomolecules and contrast agents. Despite the fact that initial studies in this area were performed on phospholipid vesicles, there is an ever-increasing interest in the use of other molecules to obtain smart vesicular carriers focusing on strategies for targeted delivery. These systems can be obtained using newly synthesized smart molecules, or by intelligent design of opportune carriers to achieve specific delivery to the site of action.